Estudo taxonômico de Scinax nebulosus (SPIX, 1824) e Scinax constrictus (LIMA, BASTOS E GIARETTA, 2004) (ANURA, HYLIDAE) com base em parâmetros morfológicos e acústicos - TAKAZONE, André Masahide Guimarães (2015)
The genus Scinax Wagler, 1830 (Hylidae, Hylinae, Dendropsophini) is represented by slightly more than 100 species, having several meanings and being described for a long time under different taxonomic categories before consolidating as a genus. Several works have suggested the redescription of several species into groups of species, and knowing that the genus is marked by high similarity and morphological conservation, some authors pointed out that species such as S. nebulosus and S. constrictus could be part of a species complex in difficulties of discriminating them only on the basis of their original descriptions. The objectives of the present work were to analyze, identify and characterize spatial patterns of morphological and acoustic variation in population samples of S. nebulosus and S. constrictus along their geographic distributions and compare aspects of external morphology, size and body shape and adult ad singing of S. nebulosus and S. constrictus to provide more consistent diagnosis for these taxa. In the comparative analyzes we used multivariate methods such as non-parametric multivariate analysis (PERMANOVA), main component analysis (PCA) and canonical variable analysis (CVA). Our results showed that S. nebulosus and S. constrictus are species that present low morphological and bioacoustic variability (ad canto). These differences were not considered diagnostic enough to permit the safe distinction between these species, so that the differences found should be attributed to intrapopulational variations. Our conclusion is that S. constrictus should be considered a junior synonym of S. nebulosus.